EDUKASI TERKAIT PENCEGAHAN DAN TATALAKSANA STUNTING PADA IBU DENGAN BALITA STUNTING DI KECAMATAN AROSBAYA, KABUPATEN BANGKALAN MADURA - Eighty Mardiyan Kurniawati; Irwanto Irwanto; Nur Anisah Rahmawati; Cahyani Tiara Safitri; Agde Muzaky Kurniawan; Rosda Rodhiyana; Ahila Meliana; Vina Firmanty Mustofa; Nabilah Khansa (Jurnal Abdi Insani, 2023)
Stunting is still a major public health problem in the community. Based on the SSGI 2021 survey, the stunting rate in Bangkalan is quite high, reaching 38.9 percent, which is still above the prevalence in East Java of 23.5. This community service program aims to help increase knowledge of cadres, mothers with stunting toddlers and the public health center in the context of stunting prevention and management. The method of implementing community service is by organizing outreach activities that involve cadres, health centers and mothers with stunting toddlers. The number of cadre and mothers of toddlers with stunting who attended were 20 mothers. There are 5 representatives from the public health center. The activity is carried out by providing education by pediatricians and obstetricians. The material provided is in the form of prevention and management of stunting in children and prevention of stunting since pregnancy. The results of the evaluation showed that not all mothers with stunted toddlers understood the condition of their children who were detected as stunted even though the public health center reports stated that. Mothers also do not understand the definition of stunting. Community service programs that are carried out can explore problems that exist in the community. The activities carried out also have a positive impact on the knowledge of mothers with stunting toddlers, cadres and the public health center.